Media Komunikasi Ilmiah Lisan - ., Sunarjanto (Responsibilitas, 2010)
Abstract Communication is one of the basic human needs, because the people will not be able to live well without communicating with other people. In philosophies, real people communicate means to humanize themselves and others. Also it seems humans have a natural urge to find out anything. He is blessed with that never curiosity goes out of his life before the fire goes out. Therefore, knowing it is a source of happiness. The more we know, the more we feel happy!. Keywords: komunikasi,lisan.